Removal of dissolved organic matter from the woodchip bioreactor start-up by foam fractionation - Mathis von Ahnen; Colin A. Stedmon; Adam C. Hambly (Water Science and Technology, 2023)
Denitrifying woodchip bioreactors are passive, low-tech systems primarily designed to remove nitrate from shallow ground waters as well as point source discharges. Despite their capacity to achieve constant nitrate removal over several years, natural aquatic environments may be affected by the leaching of dissolved organic matter (DOM) from fresh woodchips during start-up. Simple on-site measures might reduce the woodchip leachate during start-up and thus add to the overall environmental sustainability of woodchip bioreactor installations. The aim of the study was to investigate whether foam fractionators could provide an effective solution. Water was flowed through fresh laboratory-scale woodchip bioreactors and recirculated through foam fractionators for 11 days. The bioreactors removed nitrate but increased phosphate and ammonia, which were not effectively removed via foam fractionation. However, foam fractionation did remove 37.8 ± 4.7% of the dissolved chemical oxygen demand (CODdiss) leached during the first 11 days of operation. Fluorescence spectroscopy revealed that the DOM composition differed between the foam and water, where the foam fraction contained higher amounts of DOM associated with the highest bioavailability and hence the greatest potential environmental impact. Optimised foam fractionators could therefore help to reduce the environmental impact of DOM leachate from woodchip bioreactors during start-up. HIGHLIGHTS Foam fractionation removed dissolved organic matter leaching from newly installed laboratory woodchip bioreactors.; Fluorescence spectroscopy revealed that the dissolved organic matter's composition differed between foam and water.;